Tiny house characteristics in Indonesia based on millennial’s user preference - Fabiola Chrisma Kirana Analisa; Satoshi Okada (Urban, Planning and Transport Research, 2023)
ABSTRACTTiny house (TH) characteristics in Indonesia based on Millennial’s user preference (MUP) were presented. The characteristic of population, type of generation, and each city characteristic were first investigated for deciding MUP. Next, TH was investigated by analysing preferred housing sizes and prices based on MUP. Qualitative and quantitative analyses were conducted by an exploratory approach on textual and internet sources with a combination of quantitative online surveys with a statistical approach. As a result, the MUP was still firmly dominated by the stereotype of living in a big house with a large land area. In contrast, the realistic housing sizes and prices were narrowed down to a small house with a limited facilities compared to the stereotype-preferred house. Using Chi-square, TH that fits the MUP resulted in a combination of the price under 500 million Rupiah (approx. 33,695 USD) with a size of 60–80 m2. Preferably a below 80 m2 property size, limited space in urban areas is able to be optimized as a settlement by applying the TH concept in Indonesia. By having such a house in urban areas, TH supports millennial’s modern cultural habits resulting in a high quality of living for productive generation of Indonesia.